Submergence in broad-crested weirs using 1D classical Hydraulics equations - Raúl Sánchez; Luis Juana (Ingeniería del Agua)
An analitycal procedure is proposed to study the submergence of broad-crested weirs by means of the Momentum Equation. Both the modular limit of the weir and the flow-rate discharge curve in non-submerged condition are calculated numerically. Head losses due to friction on the weir are considered. The results of the calculation have been experimentally contrasted in the laboratory on a truncated weir. The submerged condition obtained by the procedure, as well as Discharge Equation, can be adjusted by an exponential equation for ease of use. The determination of the submergence condition of a broad-crested weir is now based on the application of the principles of Hydraulics. Thus, weir project and the limit of application of the Discharge Equation are improved.